Vibration suppression of nonlinear laminated composite plates using internal oscillator-enhanced nonlinear energy sinks. (15th March 2023) - Zhang, Wei-Xing; Zhang, Wei; Yang, Dong-Shuo; Luo, Zhong; Guo, Xiang-Ying
Highlights: A novel nonlinear energy sink with internal oscillator (NES-IO) is applied to the low frequency vibration control. The vibration reduction mechanism of the NES-IO is analyzed. The correctness of the analytical results is verified by numerical results. The NES-IO has obvious advantages under large energy vibration. Parameter selection of oscillators is very important for optimizing the absorber. Abstract: This paper concerns an investigation into the excessive vibration control of laminated composite plates using a nonlinear energy sink with internal oscillator (NES-IO). The proposed NES-IO can suppress vibration more effectively than traditional NES measured by both energy dissipation and frequency responses. Based on the first-order shear deformation theory and the Galerkin method, the dynamic model of the nonlinear laminated composite plate with the NES-IO is established. Then, the mechanism of the NES-IO is analyzed, and the internal oscillator improves the vibration reduction performance of the absorber, especially with large amplitude excitations. Through comparing the NES-IO with the traditional NES, it is found that the effective vibration reduction range of the NES-IO under shock excitation is wider. Moreover, the slow flow equations of the system are derived by the complexification-averaging method, and the result is verified by the Runge-Kutta method. It is also found that the NES-IO has a great advantage in suppressing the occurrence of higher branch responses through the frequency-responses analysis. Furthermore, the influences of the parameters of the grounded and internal oscillators on the vibration suppression are also discussed to optimize the NES-IO structure.